The position of common languages in Afghanistan in the last two centuries - Mahboob, Muhibullah; Assadullah Qatey; Shejauddin Hanif (Science and Education, 2024)
Afghanistan has been called as the “crossroads of ancient cultures” due to its geostrategic and geopolitical sensitive location. Afghanistan has hosted dozens of civilizations throughout history. Various ethnic groups live in Afghanistan, such as Pashtuns, Tajiks, Uzbeks, Turkmens, Baloches, Imaqs, Kazakhs, Kyrgyzes, Peshaiis, Nuristani, Pamiri, etc. These ethnic groups have been living together for a long time. The official languages of Afghanistan are Persian (officially called Dari) and Pashto. Next to Pashto and Persian, the most widely spoken languages in Afghanistan are Turkish languages (Uzbek, Turkmen, Kyrgyz and Kazakh), which are widely used in northern Afghanistan. In addition to these languages, there are other languages spoken by other ethnic minorities in this country. Unfortunately, in the last two centuries, the common languages in this land have experienced many ups and downs. In order to protect the different languages of this country, the constitution of Afghanistan was amended again in 2004, and despite these efforts, language remains a controversial issue in Afghanistan that often forces the ethnic groups living in this land into confrontation with each other.